Bearing Capacity Factors for Rough Conical Footing by Viscoplasticity Finite-Element Analysis - Phuor, T. (American Society of Civil Engineers (ASCE), 2022)
Many researchers have computed the bearing capacity of the strip and circular footings resting on the soil with the low and medium friction angle (Ï â¤ 35Â°) by employing the finite-element method (FEM). It is reported that the numerical instability occurs with the high value of Ï. Thus, based on the suggested values of soil dilation angle (Ï) in this study, the numerical computation can be achieved for all Ï. Therefore, this paper presents the computation of the vertical bearing capacity factors Nc, Nq, and NÎ³ of a rough conical footing placed on the soil with friction angle ranging from Ï = 5Â° to 45Â° by using the FE-based viscoplastic strain method under the Mohr-Coulomb (MC) yield criterion. The numerical simulations are solved using in-house MATLAB codes. The effects of the cone apex angle (Î²) and Ï on the bearing capacity are examined thoroughly by the computation of factors individually and compared with the available solutions. The current solutions are found to be in good agreement for Nc, Nq, NÎ³ values; however, the discrepancies are also observed and presented. Therefore, the bearing capacity factor charts are established, and, consequently, the ultimate load of the footing can be determined by using the superposition assumption in Terzaghi's equation. Â© 2021 American Society of Civil Engineers.